Wireless sensor network for monitoring irrigation using XBee Pro S2C - Gita Indah Hapsari; Giva Andriana Mutiara; Luky Rohendi; Aldy Mulia (Institute of Advanced Engineering and Science, 2020)
Monitoring irrigation is still the problem of agriculture in Indonesia. During the dry season, the farming fields drought while in the rainy season, floods happened. Since the farm-fields located far from the urban area, it requires an automatic tool for monitoring the availability of water that can help the farmer to monitor the farm-field. Wireless sensor network is an appropriate technology used to overcome problems related to the monitoring system. This research is using a water level sensor, pump, Arduino Nano, and XBee Pro S2C in each monitoring node. The system designed within two modules, an automation irrigation module and a monitoring module, which is connected with the communication configuration of master-slaves between Xbee Pro S2C at each node. The system examined several scenarios in order to test the performance. Based on the testing result, all the performance parameters can be adequately delivered to the user and appropriated with the real condition in the farm field. The delay between nodes only takes 5-10 seconds.